The gender lifetime earnings gap—exploring gendered pay from the life course perspective - Boll, Christina; Jahn, Malte; Lagemann, Andreas (Journal of Income Distribution®, 2017)
Research on the gender earnings divide so far mostly focuses on the gender gap in hourly wages, which due to its snapshot nature is unable to capture the biographical dimension of gendered pay. With the ‘gender lifetime earnings gap’ (GLEG), we introduce a new measure that fills this gap. Based on a group of 72,085 German individuals born 1950-64 from the ‘Sample of Integrated Labor Market Biographies’ (SIAB 7510), we find that at the end of the employment career, women accumulate 46.6% less earnings than men. Thus, the GLEG is more than twice as high as the current German gender pay gap. The GLEG is higher at the bottom than at the top of the earnings distribution. It most prominently widens during the period of family formation (age 25-35). Relatedly, gender differences in endowments, mainly in terms of experience and hours, account for almost two-thirds of the GLEG. For younger cohorts, family breaks tend to lose importance, whereas the role of work hours remains unchanged. Moreover, women in younger cohorts approach men with respect to employment, education and sector premiums.